Global Rates of Subaerial Volcanism on Earth - Papale, Paolo; Garg, Deepak; Marzocchi, Warner (Frontiers in Earth Science, 2022)
Knowledge of the global rates of volcanism is fundamental for modeling the Earth, as those rates closely relate to plate tectonics, crustal growth, mantle dynamics, atmospheric evolution, climate change, and virtually any aspect of the global Earth dynamics. In spite of their huge relevance, the global rates of volcanism have remained unknown, hidden within data that appeared disordered, largely fragmented and incomplete, reflecting poor preservation of small eruptions in the geological record, rareness of large eruptions, and distributions far from normal. Here we describe and validate a model that reproduces global volcanism to high statistical significance, and that is so simple to comfortably fit on a t-shirt. We employ the model to compute the expected rates of global terrestrial volcanism over time windows from 1 to 100,000 years, and validate it by comparing with observations back to a few million years. Notably, the model can be tested against independent observations collected in the near future, a feature which is relatively uncommon among global models of Solid Earth dynamics.